Chronologia osadnictwa szeleckiego na stanowisku Lubotyń 11, pow. głubczycki, w świetle bayesowskiego modelowania datowań - Bobak, Dariusz; Połtowicz-Bobak, Marta; Jary, Zdzisław; Raczyk, Jerzy; Moska, Piotr (Muzeum Okręgowe w Rzeszowie, 2016)
This article attempts to clarify the Szeletian chronology of the site Lubotyń 11 on the Głubczyce Plateau. The site, maintained in a good condition, has a series of radiocarbon and OSL dating. By the use of the method of Bayesian modelling, a model has been constructed, taking into account the stratigraphic relationships between the natural and cultural events observed at the site. It allowed us to restore the history of the site and, in particular, to establish two facts regarding the Palaeolithic settlement. Although the site is a remnant of multiple stays of human groups, and the flint material clearly indicates the presence of older and younger Szeletian phase, now it is not possible to separate chronologically settlement episodes. The established beginning of the settlement appears to be the earliest known chronological point within the operation of the Szeletian culture.
Chronology of the Szeletian settlement at the site Lubotyń 11, Głubczyce district, in the light of Bayesian modelling of dating
Keywords: age modelling; bayesian method; chronology; middle to upper palaeolithic transition; Szeletian; Silesia